Prevalence, antimicrobial susceptibility, and genotyping of Streptococcus agalactiae in Tilapia fish (Oreochromis niloticus) in Egypt - Alazab, Asmaa; Sadat, Asmaa; Younis, Gamal (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: Streptococcus agalactiae is a zoonotic human and animal pathogen that causes global economic losses in aquaculture and fatal outcomes in Tilapia. This study aimed to identify S. agalactiae isolated from different fish sources intended for human consumption phenotypically and genotypically and to characterize the virulence-associated genes fbsA (fibrinogen-binding protein FbsA), cfb (CAMP factor), and pbp1A/ponA (penicillin-binding protein 1A). Materials and Methods: Three hundred Nile Tilapia fish (Oreochromis niloticus) were collected from different farms and retailshopsin Dakahlia and Damietta, Egypt, during the summer of 2020. The samples were examined using routine phenotypic methods, then characterized using polymerase chain reaction (PCR) targeting S. agalactiae-specific dltS gene. All S. agalactiae isolates were examined for the susceptibility to ten antimicrobial agents by the disc diffusion method. The virulence-associated genes (fbsA, cfb, and pbp1A/ponA) were characterized using multiplex-PCR. Results: Streptococcus agalactiae was detected in 7% (n = 21/300) samples. The isolates showed high resistance against ampicillin and erythromycin (20/21; 95%) for each. The most predominant antibiotypesthrough isolates were P, CN, SXT, CRO, TE, CTX, E, AMP, at 10.5% for each antibiotype. A total of 19 (90.5%) of S. agalactiae isolates showed multi-drug resistance (MDR), and those were recovered from market Tilapia fish. The virulence-associated genes (fbsA, cfb, and pbp1A/ ponA) were identified in the S. agalactiae as 100%, 76%, and 52%, respectively. Conclusions: The MDR S. agalactiae detected in raw Tilapia fish pose a significant health hazard to consumers due to their zoonotic characteristics. J. Adv. Vet. Anim. Res., 9(1): 95–103, March 2022 http://doi.org/10.5455/javar.2022.i573